When Forgetting Preserves Memory - Hupbach, Almut (Frontiers in Psychology, 2013)
There has been a resurgence of interest in defining the circumstances leading to memory modifications. Studies have shown that reactivating a supposedly stable memory re-introduces a time-limited window of plasticity during which presentation of interfering material can cause long-term memory changes. The present study asks whether such memory changes can be prevented if people are instructed to forget the memory before the new material is encoded. Participants learned a set of objects. After 48 hours, they were reminded of this learning episode, and learned another set of objects. Again 48 hours later, they recalled the first (Exp. 1) or second set (Exp. 3). As shown previously, a reminder caused intrusions from the second set into recall of the first set. Here I show that the instruction to forget the first set significantly diminished intrusions from the second set, especially when the instruction was given before the new set was encoded in the second session. Experiment 2 suggests that the reduced intrusions were due to list segregation/isolation, rather than temporarily inhibited access to Set 1. Taken together, the study shows that the attempt to forget a memory can immunize it such that the presentation of interfering material has limited effects, and the memory can be recalled unchanged in the future. This is important when veridical memory is essential, such as in eyewitness testimonies.